Studies of Time-like Electromagnetic Structure of Baryons with HADES - Ciepał Izabela (EPJ Web of Conferences, 2024)
We present results of studies of Dalitz decays of baryon resonances (R→Ne+e−) in proton-proton (pp) and pion-proton (πp) collisions performed by the HADES collaboration. They provided the first measurement of electromag netic transition form factors of baryons in the time-like region and contribute to the understanding of the photon-baryon coupling and the role of Vector Dom inance Model in a baryonic sector. We discuss also implications of the results to the understanding of the emissivity of dense and hot QCD matter created in heavy-ion collisions and the role played by the in-medium modification of the ρ meson. Further prospects for future studies with pion beams at GSI with HADES are given in the outlook.